The association between non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio and the risk of insulin resistance: results from the NHANES 2003–2016 - BaoYing Li; YuLing Zha; Mi Deng; LuNa Niu; XueFei Li; RuoWei Zhu; Jing Tian; Lu Jing (BMC Endocrine Disorders)
Abstract Background The relationship between non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio (NHHR), as a novel lipid indicator, and insulin resistance (IR) remains unclear. This cross-sectional study aimed to identify the association between NHHR and the risk of IR. Methods Utilizing NHANES data from 2003 to 2016, 5,853 participants were eventually included. Triglyceride glucose index (TyG) was used as a marker to evaluate IR, and weighted logistic regression, trend test, restricted cubic spline and subgroup analysis were used to analyze the relationship between NHHR and the risk of IR. Results After adjusting for all relevant covariates, NHHR exhibited a significant positive correlation with TyG (OR = 3.44, 95% CI: 3.12–3.80, P < 0.001). The restricted cubic spline further proved that NHHR had nonlinear correlation with TyG. Subgroup analyses suggested distinct differences and cross-correlations between race and smoking status, and could provide reference for studies of multicharacteristic populations. Conclusion This cross-sectional study revealed a significant association between NHHR and the risk of IR. Elevated NHHR was associated with an increased risk of diminished insulin sensitivity and the risk of IR development, and these findings provided a clinical perspective for understanding the pathogenesis of IR from cholesterol accumulation. Clinical trial number Not applicable.